A prevalência do bullying entre adolescentes e seu impacto social - Lopes, Gustavo Pereira [UNESP] (2017)
Bullying is considered a subtype of violence and is characterized by negative actions by one or more individuals in an unequal power relationship. This issue should be broadly discussed in the scientific setting as it may develop sequels that extend into adulthood bringing personality problems and socialization. The objective of this research was to verify the prevalence of bullying in a representative sample of adolescents. The study was of the cross-sectional epidemiological type of school base. The study included adolescents aged 11 to 16 enrolled in the public school system of a medium-sized municipality in northwest São Paulo. Bullying was assessed using the Kidscape questionnaire. Data were analyzed through descriptive and analytical statistical analysis. According to the results, 48.22% of the adolescents participating in the research had already suffered from bullying, and the most prevalent form of bullying was verbal (46.56%), where the majority were boys (65.14%). Conclude a high prevalence of bullying, with predominance in the male sex and verbal bullying, where prevention practices could change these results